2015
DOI: 10.1128/iai.02895-14
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Caspase-11 by Aspartyl Proteinases of Candida albicans and Implication in Promoting Inflammatory Response

Abstract: We recently demonstrated that the secreted aspartyl proteinases (Saps), Sap2 and Sap6, of Candida albicans have the potential to induce the canonical activation of the NLRP3 inflammasome, leading to the secretion of interleukin-1␤ (IL-1␤) and IL-18 via caspase-1 activation. We also observed that the activation of caspase-1 is partially independent from the NLRP3 activation pathway. In this study, we examined whether Sap2 and Sap6 are also able to activate the noncanonical inflammasome pathway in murine macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 35 publications
(60 reference statements)
0
48
0
1
Order By: Relevance
“…In mouse models of vaginal infection, some Saps (mostly Sap2 and Sap6, or Sap5, depending on the model [33,39]), appear to be responsible for the expression of key immunopathogenic markers of landmark inflammatory events. This includes polymorphonuclear (PMN) cell infiltration and production of pro-inflammatory cytokines, such as IL-1β and IL-18, via the activation of inflammasome-mediated caspase-1 and possibly other caspases [41]. The use of individual or collective subfamily SAP knockout strains, human anti-Sap Fragment antigen binding (Fab), and whole transcriptome analyses has shown that inflammation in vaginal disease can be dampened either downstream, by pharmacological inhibition of NLRP3 inflammasome and blockade of IL-1β receptor, or upstream, by specifically affecting Sap production or activity by anti-Sap antibodies or pepstatin A, without affecting the infectious fungus burden [38,39] (Fig 3).…”
Section: A Blend Of Immunoevasion and Immunoactivationmentioning
confidence: 99%
“…In mouse models of vaginal infection, some Saps (mostly Sap2 and Sap6, or Sap5, depending on the model [33,39]), appear to be responsible for the expression of key immunopathogenic markers of landmark inflammatory events. This includes polymorphonuclear (PMN) cell infiltration and production of pro-inflammatory cytokines, such as IL-1β and IL-18, via the activation of inflammasome-mediated caspase-1 and possibly other caspases [41]. The use of individual or collective subfamily SAP knockout strains, human anti-Sap Fragment antigen binding (Fab), and whole transcriptome analyses has shown that inflammation in vaginal disease can be dampened either downstream, by pharmacological inhibition of NLRP3 inflammasome and blockade of IL-1β receptor, or upstream, by specifically affecting Sap production or activity by anti-Sap antibodies or pepstatin A, without affecting the infectious fungus burden [38,39] (Fig 3).…”
Section: A Blend Of Immunoevasion and Immunoactivationmentioning
confidence: 99%
“…Candida albicans is a pathogenic yeast that induces candidiasis and secretes aspartyl proteinases, which are the key determinants for its pathogenesis. Of the several types of secreted aspartyl proteinases, secreted aspartyl proteinase 2 and secreted aspartyl proteinase 6 were reported to play a critical role in the activation of the caspase-11 non-canonical inflammasome i.e., they induced the activation of caspase-11 non-canonical inflammasome in macrophages in a type I IFN-dependent manner [28]. This study provides the insight that not only Gram-negative bacteria, but also yeast can activate the caspase-11 non-canonical inflammasome in the inflammatory responses.…”
Section: Activatorsmentioning
confidence: 99%
“…However, only the live and not the attenuated yeast strongly suppressed some of the crucial virulence factors of C. albicans, such as its capacity to switch from the yeast to the hyphal form and the ability to express aspartyl proteases Gabrielli et al, 2018). These effects were related to the ability of the live yeast to significantly inhibit the expression of two important hyphal growth-associated genes, in particular the hyphal wall protein 1 (HWP1) and extent of cell elongation 1 (ECE1), as well as the expression of two secretory aspartyl proteinases (SAPs), SAP2, and SAP6, which play a key role in the immunopathogenesis of vaginal candidiasis (Naglik et al, 2003;Cassone and Cauda, 2012;Gabrielli et al, 2015;Pericolini et al, 2015;Roselletti et al, 2017). The suppression of SAP2 and SAP6 gene expression mirrored the reduction of the inflammatory process associated with the pathogenesis of Candida vaginitis .…”
Section: Saccharomyces Cerevisiae-based Probiotic Effects On Vaginal mentioning
confidence: 99%